EFFECT OF INTEREST RATE, INFLATION AND NATIONAL INCOME TO RUPIAH THE AMERICAN DOLLARS IN 2006-2016 - Muhammad Irsyad Mustaqim; Saparuddin Mukhtar; Tuty sariwulan (Jurnal Ilmiah Econosains, 2017)
This research aims to analyze the effect of interest rates, inflation and national income against the rupiah exchange rate over the US dollar. As for the data used in this research is secondary data, with this type of time series data in the period 2006-2016 obtained from Bank Indonesia and the World Bank. The method of this research method using exposÃ© facto. Data analysis techniques used in this research is the analysis of multiple regression. By using multiple regression analysis model, the output shows that interest rates (X 1) positive and significant effect of the exchange rate of the rupiah against the US dollar up (Y). Inflation rate (X 2) do not affect the exchange rate of the rupiah significantly to top u.s. dollars (Y). National income (X 3) a positive effect of the exchange rate of the rupiah against the US dollar up (Y). Of test results by looking at their significance value F = 0.000 then it can be said to be 0.05 < simultaneously interest rates, inflation and national income effect significant at Î± = 5% against the rupiah exchange rate over the US dollar in the year 2006-2016. The value of the coefficient of determination (R2) acquired for 0.660 has a sense that the rupiah exchange rate over the US dollar can be explained by the level of interest rates, inflation and national income amounted to 66% while the rest is explained by other factors that do not exist in the model for this research.